2015
DOI: 10.1016/j.bbrc.2014.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase 6 mediates TNFα-induced endothelial barrier dysfunction

Abstract: A key event in the progression of systemic inflammation resulting from severe trauma or shock involves microvascular hyperpermeability, which leads to excessive plasma fluid and proteins accumulating in extravascular space resulting in tissue edema. The precise molecular mechanism of the hyperpermeability response is not completely understood. Protein tyrosine kinase 6 (PTK6, also known as breast tumor kinase BRK) is a non-receptor tyrosine kinase related to Src-family proteins. Although it has also been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This response was small, reflecting approximately 10–15 % difference in norm resistance. Reduced TEER over this period has been reported by others [ 32 , 33 ]. After this acute period, the barrier resistance of the HCMVECs increased in a cytokine, concentration and time-dependant manner.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This response was small, reflecting approximately 10–15 % difference in norm resistance. Reduced TEER over this period has been reported by others [ 32 , 33 ]. After this acute period, the barrier resistance of the HCMVECs increased in a cytokine, concentration and time-dependant manner.…”
Section: Discussionsupporting
confidence: 77%
“…After this acute period, the barrier resistance of the HCMVECs increased in a cytokine, concentration and time-dependant manner. This strengthening of the barrier occurs over a period, which is (surprisingly) omitted in other ECIS studies [ 32 , 33 ]. The magnitude of the increase in barrier resistance is greater and occurs for longer for TNFα.…”
Section: Discussionmentioning
confidence: 98%
“…19 TNF-α, one of the major pro-inflammatory cytokines, promotes inflammatory cell infiltration, induces vascular endothelial cell injury, and enhances the generation of ROS. 20 Here, we found that GLA treatment reduced the production of several pro-inflammatory cytokines, including TNF-α, IL-1β, and IL-6 in In the present study, we showed that GLA treatment suppressed p38 phosphorylation and NF-κB activation in H 2 O 2 -induced HCASMCs.…”
Section: Glaucocalyxin a Attenuates P38 And Nf-κb Activation In H 2supporting
confidence: 60%
“…With regards to nonreceptor tyrosine kinases, as noted earlier, Fer-kinase associates to an amino-terminal region of p120 (amino acids 131–156), between p120’s 3 rd and 4 th translational start sites (Figure 1) (Kim and Wong, 1995), with Src and Fyn sites mapped relatively nearby to Y112, Y217 and Y228. Recently, the non-receptor tyrosine kinase PTK6 (Protein receptor tyrosine kinase 6) was found in association with p120-catenin, although its phosphorylation of p120-catenin has yet to be characterized (Haines et al, 2015). …”
Section: Phosphorylation Of P120-cateninmentioning
confidence: 99%